2010
DOI: 10.1002/stem.530
|View full text |Cite
|
Sign up to set email alerts
|

Neuronatin Promotes Neural Lineage in ESCs via Ca2+ Signaling

Abstract: Neural induction is the first step in the formation of the vertebrate central nervous system. The emerging consensus of the mechanisms underling neural induction is the combined influences from inhibiting bone morphogenetic protein (BMP) signaling and activating fibroblast growth factor (FGF)/Erk signaling, which act extrinsically via either autocrine or paracrine fashions. However, do intrinsic forces (cues) exist and do they play decisive roles in neural induction? These questions remain to be answered. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 51 publications
3
80
0
Order By: Relevance
“…Existing literature suggests the involvement of neuronatin in the regulation of glycogen and lipid metabolism, and its mutation is associated with obesity (31,32,37,39). The primary and secondary structure of neuronatin is also strikingly similar with phospholamban (an ER-resident Ca 2ϩ regulator found in cardiac muscle), and recent reports have demonstrated that it is indeed involved in increasing the intracellular Ca 2ϩ by antagonizing SERCA2 pump in the ER (27,38). We have also detected a significant increase in intracellular Ca 2ϩ in neuronatin-transfected neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Existing literature suggests the involvement of neuronatin in the regulation of glycogen and lipid metabolism, and its mutation is associated with obesity (31,32,37,39). The primary and secondary structure of neuronatin is also strikingly similar with phospholamban (an ER-resident Ca 2ϩ regulator found in cardiac muscle), and recent reports have demonstrated that it is indeed involved in increasing the intracellular Ca 2ϩ by antagonizing SERCA2 pump in the ER (27,38). We have also detected a significant increase in intracellular Ca 2ϩ in neuronatin-transfected neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Neuronatin is highly expressed in neonatal brain and possibly involved in neural induction and neuronal differentiation during brain development (27,38). In adult mice, it is also found to be selectively expressed in various limbic structures (31) of brain and several non-neural tissues including skin (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, an increase in [Ca 2+ ] i also appears to be the key signal that controls neural fate determination [93]. However, while the main source of Ca 2+ increase in amphibian ectoderm is influx through voltage-operated Ca 2+ channels, mammalian embryonic stem cells do not express VOCCs and therefore must employ alternate pathways [94,95].…”
Section: Physiological Roles Of Ca2+ Signaling In Neural Developmentmentioning
confidence: 99%
“…However, at the time of that study, the molecular identity of the SOC had not yet been determined and the potential role of the CRAC channel family in mediating these store-operated currents was not evaluated. More recently, a screen to identify neural induction genes in mammals identified neuronatin (Nnat), an ER membrane protein that physically antagonizes SERCA2 activity to regulate the intracellular Ca 2+ level [93]. Knocking down Nnat inhibits neural induction in ESCs by reducing the level of intracellular Ca 2+ .…”
Section: Physiological Roles Of Ca2+ Signaling In Neural Developmentmentioning
confidence: 99%